Chronic Subordinate Colony Housing Paradigm: A Mouse Model to Characterize the Consequences of Insufficient Glucocorticoid Signaling - Langgartner, Dominik; Füchsl, Andrea M.; Uschold-Schmidt, Nicole; Slattery, David A.; Reber, Stefan O. (Frontiers in Psychiatry, 2015)
Chronic, in particular chronic psychosocial, stress is a burden of modern societies and known to be a risk factor for numerous somatic and affective disorders (in detail referenced below). However, based on the limited existence of appropriate, and clinically-relevant, animal models for studying the effects of chronic stress, the detailed behavioural, physiological, neuronal, and immunological mechanisms linking stress and such disorders are insufficiently understood. To date, most chronic stress studies in animals employ intermittent exposure to the same (homotypic) or to different (heterotypic) stressors of varying duration and intensity. Such models are only of limited value, since they do not adequately reflect the chronic, and continuous, situation that humans typically experience. Furthermore, application of different physical or psychological stimuli renders comparisons to the mainly psychosocial stressors faced by humans, as well as between the different stress studies almost impossible. In contrast, rodent models of chronic psychosocial stress represent situations more akin to those faced by humans and consequently seem to hold more clinical relevance. Our laboratory has developed a model in which mice are exposed to social stress for 19 continuous days, namely the chronic subordinate colony housing (CSC) paradigm, which bridges this gap. The main aim of the current review article is to provide a detailed summary of the behavioural, physiological, neuronal and immunological consequences of the CSC paradigm, and wherever possible relate the findings to other stress models and to those from human studies.